VLADIMIR NAZOR’S PARTISAN POEMS: A READING FROM THE CAPITALIST PRESENT - Maša Kolanović (Filolog, 2025)
This paper presents a comparative analysis of the poetry collection Partisan poems (Pjesme partizanke) by the Croatian poet Vladimir Nazor, written during the People’s Liberation Struggle and published in 1944, and the Occupy Wall Street Poetry Anthology (Boyer and Marinovich, 2011), written in the context of protests related to the last global economic crisis of 2008, also known as the Great Recession. In the comparative reading of these two poetry collections, the analysis is focused on the structural and political relationship between poetry and revolutionary imagery in the context of form, images, and effects. Following recent theoretical research in literature on the topic of poetry, revolution and Partisan art (e.g., Bernes, 2022; Komelj, 2009, Kirn, 2020), the analysis traces specific strategies in the poetic production of political imaginary of a revolutionary quality in the immediate poetic responses to the Second World War and the global economic crisis, with a special emphasis on the formation of the idea of “poetic justice” (Nussbaum, 1997) and the “impossible” (Komelj, 2009) when it comes to imagining the future of overcoming both of the crisis events in which these collections were created.